Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 36

Answer

y=0

Work Step by Step

5y + -3(y + -2) = 6(y + 1) Reorder the terms: 5y + -3(-2 + y) = 6(y + 1) 5y + (-2 * -3 + y * -3) = 6(y + 1) 5y + (6 + -3y) = 6(y + 1) Reorder the terms: 6 + 5y + -3y = 6(y + 1) Combine like terms: 5y + -3y = 2y 6 + 2y = 6(y + 1) Reorder the terms: 6 + 2y = 6(1 + y) 6 + 2y = (1 * 6 + y * 6) 6 + 2y = (6 + 6y) Add '-6' to each side of the equation. 6 + -6 + 2y = 6 + -6 + 6y Combine like terms: 6 + -6 = 0 0 + 2y = 6 + -6 + 6y 2y = 6 + -6 + 6y Combine like terms: 6 + -6 = 0 2y = 0 + 6y 2y = 6y Solving 2y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 2y + -6y = 6y + -6y Combine like terms: 2y + -6y = -4y -4y = 6y + -6y Combine like terms: 6y + -6y = 0 -4y = 0 Divide each side by '-4'. y = 0 Simplifying y = 0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.